2007
DOI: 10.1051/agro:2006032
|View full text |Cite
|
Sign up to set email alerts
|

Alternative sugar beet production using shallow tillage and municipal solid waste fertiliser

Abstract: -The application of conventional agricultural practices, e.g. deep soil tillage and repeated, plentiful mineral fertilisation, can lead to a progressive deterioration of soil fertility, especially in Mediterranean environments characterised by scanty rains and high summer temperatures. As a consequence, to maintain high levels of both crop productivity and soil organic matter and to improve some soil properties, a reduction of agricultural inputs and a greater supply of organic material are needed. In the ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…It has been reported that organic matter accumulation in soil was more than double due to compost application than the same amount of raw organic material (Food and Fertilizer Technology Centre, 1997). Similarly, Montemurro et al (2007) reported a significant increase in the organic C contents in soil treated with municipal solid waste compost compared with mineral fertilizer. A greater amount of stable aggregate fraction of 24.8%, remaining in the 1.0 mm sieve, was found in soil treated with the enriched compost after 56 days of incubation compared with soil treated with the raw organic wastes or untreated soil (Tab.…”
Section: Effect Of Enriched Compost On Soil Conditioningmentioning
confidence: 89%
“…It has been reported that organic matter accumulation in soil was more than double due to compost application than the same amount of raw organic material (Food and Fertilizer Technology Centre, 1997). Similarly, Montemurro et al (2007) reported a significant increase in the organic C contents in soil treated with municipal solid waste compost compared with mineral fertilizer. A greater amount of stable aggregate fraction of 24.8%, remaining in the 1.0 mm sieve, was found in soil treated with the enriched compost after 56 days of incubation compared with soil treated with the raw organic wastes or untreated soil (Tab.…”
Section: Effect Of Enriched Compost On Soil Conditioningmentioning
confidence: 89%
“…Conversely, the innovative RC technology terminates ASC by flattening them, with one or two passages of the roller crimper, leaving a thick mulch layer into which the next crop is sown or transplanted (Teasdale et al, 2012). As regards the organic fertilisers and amendments used in the experimental device, several studies have shown promising yield results from their application, particularly for municipal solid waste compost (Montemurro et al, 2005(Montemurro et al, , 2007 and anaerobic digestates in different crops. The combination with the above-described agro-ecological practices should sustain and improve the expected services to the agro-ecosystem.…”
Section: Mitiorg Long-term Experimental Devicementioning
confidence: 99%
“…In fact, the turnover rate of organic materials varies considerably, from less than 1 year, as for microbial biomass, to more than 1 thousand years of stable humus ( Van-Camp et al, 2004). The organic matter is being progressively depleted, particularly in the Mediterranean area, where the warm climate and the intensity of cultivation increase the rate of decomposition (Montemurro et al, 2007). By contrast, the build-up of organic matter in soils is a process much slower and more complex than its decline ( Van-Camp et al, 2004).…”
Section: Soil Management Strategies For a Sustainable Agriculturementioning
confidence: 99%